Study on Impression Techniques and Materials for Implant among Dentists in Erbil city: A Survey study. - Shahla Hama Rasheed Omer; Shang Hussein Muhammed; Shayma Abdulamir Mamandi; Zina Zakaria Rashid (Erbil Dental Journal)
Background and Objectives:  The Success and longevity of implant prosthesis is affected by an accurate fit which can be achieved through a proper impression technique and material, the techniques of impression taking can be made by either a closed or open tray impression procedures or by implant level impression technique. The main objective of the presented research was to investigate the most preferable impression material and technique for dental implant placement.